Lipidic cubic-phase leflunomide nanoparticles (cubosomes) as a potential tool for breast cancer management - Mariam Zewail; Passent M. E. Gaafar; Mai M. Ali; Haidy Abbas (Taylor & Francis Group, 2022)
Despite the fact of availability of several treatments for breast cancer, most of them fail to attain the desired therapeutic response due to their poor bioavailability, high doses, non-selectivity and as a result systemic toxicity. Here in an attempt made to study the transdermal effect of leflunomide (LEF) against breast cancer. In order to improve the poor physicochemical properties of LEF, it was loaded into cubosomes. Cubosomes were prepared by the emulsification method. Colloidal characteristics of cubosomes including particle size, ζ-potential, entrapment efficiency, in-vitro release profile and ex-vivo permeation were studied. In addition, morphology, stability, cytotoxicity and cell uptake in MDA-MB-231 cell line were carried out for the selected cubosomal formulation. The selected LEF loaded cubosomal formulation showed a small particle size (168 ± 1.08) with narrow size distribution (PI 0.186 ± 0.125) and negative ζ potential (-25.5 ± 0.98). Its Entrapment efficiency (EE%) was 93.2% and showed sustained release profile that extended for 24 h. The selected formulation showed stability when stored at 25 °C for three months in terms of size and EE%. TEM images illustrated the cubic structure of the cubosome. Cell culture results revealed the superiority of LEF cubosomes compared to LEF suspension in their cytotoxic effects with an IC50 close to that of doxorubicin. Furthermore, LEF cell uptake was significantly higher for LEF cubosomes. This may be attributed to the effect of nano-encapsulation on enhancing drug pharmacological effects and uptake indicating the potential usefulness of LEF cubosomes for breast cancer management.